EFL Students Responses and Expectations on Teachers’ Teaching Performance in Mister Nob English Course, Pare, Kediri - Lukman Hakim; Achmad Faqih; Yuni Putri Utami; Awati Fane; Syafira Alfiani (Jurnal Intelek Insan Cendikia, 2025)
This study investigates beginner-level EFL students’ perceptions and expectations of their teachers’ teaching performance at the Mister Nob English course. While previous research has often emphasized subject knowledge and relied on quantitative approaches in formal settings, this study adopts a qualitative method to provide deeper insight into teacher performance in an informal learning environment. Using the Teaching Competencies Scale (TCS) by Catano and Harvey (2010), the study explored nine key competencies: availability, communication, conscientiousness, creativity, feedback, individual consideration, professionalism, problem-solving, and social awareness. Data were collected from ten students through questionnaires and semi-structured interviews. Findings revealed that students responded positively to their teachers’ performance, particularly valuing social awareness and availability. However, uncertainty remained regarding feedback and problem-solving competencies. Additionally, students expressed expectations for greater creativity, punctuality, and lesson preparation. The study highlights the importance of emotional engagement, accessibility, and creativity in promoting effective teaching and learning in EFL contexts. Recommendations for future research include expanding participant diversity, incorporating teachers’ perspectives, and broadening the scope of performance indicators.